A conditional embrace—Swedish LGBTQ+ spaces through the eyes of ethnic minority non-heterosexual individuals - Miller, Emelie Louise (Frontiers in Psychology, 2022)
In research on sexuality, as well as in policy making, marginalized sub-groups within sexual minorities have often been overlooked. From the vantage point of Sweden, a country highly ranked in equity and LGBTQ+ rights, and with an increasingly diversified population, ethnic minority non-heterosexual people’s lived experiences are still very much lacking in voice and visibility. The aim of the present study was to examine experiences within Swedish non-heterosexual settings, held by ethnic minority non-heterosexual individuals. A thematic analysis of in-depth interviews with 22 Swedish non-heterosexual individuals, 13 cis-men and 9 cis-women, with diverse first- and second-generation immigration backgrounds, was conducted. Two main themes were identified. The first theme; “Constantly contested identities”, is composed of the sub-themes “Ingrained, intersecting ideals” and “Prejudiced spaces”, and the second theme; “Effects and counteractions” of the sub-themes “Never fully human” and “Representation and separatism”. The results demonstrate that ethnic minority non-heterosexual people experience problematic and intersecting ideals, with related discrimination, in various Swedish non-heterosexual spaces. This was especially true regarding ideals of whiteness, which in turn intersected with ideals connected to gender, age, beauty and fitness. Experiences of alienation, exotification and tokenism were common among the participants, and had negative psychological effects, including multiple-minority stress and a constant outsider feeling. Representation, and participation in separatist forums was utilized as primary strategies to counteract the negative effects. The findings shed light on previously under-researched and un-problematized ideals and actions within LGBTQ+ spaces in Sweden. Further research, and continued critical discussions about ethnic minority non-heterosexual people's plight within non-heterosexual settings in Sweden, and beyond, is advocated.